Study on Local Scour of Suction Bucket Foundations at Offshore Wind Farms in Shapa of Yangjiang - REN Hao; LIU Bo; LIU Xiaojian; GUO Huiqun; CHEN Chen (Renmin Zhujiang, 2022)
A normal physical model is built to study the local scour of suction bucket foundations at offshore wind farms in Shapa of Yangjiang.The results indicate that the maximum scour depth of bucket foundations under the combined action of waves and currents is greater than that under pure currents and pure waves.Under the combined action of waves and currents,the maximum scour depth appears on the side facing water and both sides of the suction bucket with slight silt on the land side,and the scoured bedform is triangular.As the scour of suction bucket foundations is mainly affected by the flow around the unearthed bucket body and bucket top's rib plates,the dredging of the bed surface before the structure is embedded can make the structure more stable,and the structure stability grows with the increase in the dredging depth.